(untitled) (Journal of Parents and Teachers, 2014)
In this article we present an experience in the subject of Ethics in 4º of ESO to address the issue of moral values. Thus, we can identify that in all the stories that have told us as children, the hero always embodied positive values and was, without a doubt, who shone and ended up triumphing.